Religion in modern Britain - Bruce, Steve (Oxford University Press, 1995)
The book will be an invaluable introduction and point of reference for students of the social sciences and religious studies. The Oxford Modern Britain series comprises authoritative introductory books on all aspects of the social structure of modern Britain. Lively and accessible, the books will be the first point of reference for anyone interested in the state of contemporary Britain. They will be invaluable to those taking courses in the social sciences